Reproductive Violence: Call Me By My Name - Zheltukha,Mariia (2024)
This paper focuses on the issue of reproductive violence as an international crime. The central question is whether the current provisions of the Rome Statute are adequate for reflecting the severity and distinct nature of reproductive violence crimes and, thus, whether these provisions can effectively support their prosecution under the new 2023 OTP Policy on Gender-Based Crimes. The prevailing misclassification of reproductive violence as a mere by-product of sexualised violence within the ICL framework obscures the unique harm inflicted, thereby contributing to significant gaps in accountability. This paper aims to highlight these gaps and advocate for explicit recognition of reproductive violence as a distinct crime under the Rome Statute in order to advance justice and protection for the victims. The research was conducted through legal analysis, supplemented by empirical data from studies by feminist scholars. It reviewed legal instruments and case law, focusing on the Rome Statute and the ICC jurisprudence, to determine how reproductive violence is currently addressed. An interdisciplinary approach was used to bring insights from IHRL and transitional justice with feminist perspectives on GBV. This paper concludes that while there are avenues within the Rome Statute to charge reproductive violence acts, the lack of direct criminalisation leads to significant challenges. Prosecuting reproductive violence acts under the open provisions, whether related to sexual violence or not, does not reflect the unique harm and the underlying value; and often contradicts the fair labelling and legality principles. For the new OTP Policy on Gender-Based Crimes to fully achieve its aim – surfacing the gender-based dimension of international crimes – the provisions of the Rome Statute should be expanded to include all the forms of reproductive violence.
Keywords: reproductive violence; international criminal law; gender-based violence; surfacing gendered crimes in international criminal law; International Criminal Court; OTP Policy on Gender-Based Crimes